Civil-Military Entanglements Anthropological Perspectives (Berghahn Books, 2019)
Military-civilian encounters are multiple and diverse in our times. Contributors to this volume demonstrate how military and civilian domains are constituted through entanglements undermining the classic civil-military binary and manifest themselves in unexpected places and manners. Moreover, the essays trace out the ripples, reverberations and resonations of civil-military entanglements in areas not usually associated with such ties, but which are nevertheless real and significant for an understanding of the roles war, violence and the military play in shaping contemporary societies and the everyday life of its citizens